PERLAWANAN PIHAK KE TIGA (DERDEN VERZET) ATAS PUTUSAN BADAN ARBITRASE NASIONAL SYARIAH (BASYARNAS) - Muhammad Rutabuz Zaman (Institut Keislaman Abdullah Faqih Gresik, 2021)
This research article describes the resistance of a third party (Derden Verzet) to the decision of the sharia national arbitration body (BASYARNAS), where we know the form of Law of the Republic of Indonesia Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution Article 60 states that, final and have permanent legal force and bind the parties